Efektivitas Pembelajaran IPS Menggunakan Video Animasi dan Kahoot! Materi Interaksi Antarnegara-Negara Asean pada Siswa Kelas VIII SMP N 3 Tebo Jambi - Pratiwi, Rahmawati; Hermanto, Fredy (Universitas Negeri Semarang, 2021)
The learning result which is not significant yet, and students who still experience handicaps and difficulties in understanding the material especially in ASEAN material. Researchers provide learning media for animated video and kahoot! in social stcience learning. This research uses quantitative method, while the research design in quasi experimental with non-equivalent control roup design. The result of this research shows that animation video and kahoot! are effective being implemented . this can be proven by seeing the effectiveness indicators such as (1) the teacher high capability to manage the classroom indicated by the score of 73 in the experimental group and 66 in the control group, (2) the teaching and learning activity which shows high activness with the score of 92,86 in the experimental group and 62,50 in the control group, (3) the increase of the learning result score of experimental group from 46,6 to 84,4 while the control group score of experimental group from 46,0 to 78,6, (4) the high responses of students towards the teaching learning activity with the experimental group score 75 and control group score 68,7.